A foam sealing strip material and preparation method thereof
By adding special porcelain auxiliary filler and porcelain filler to the silicone rubber foam sealing strip material, the silicone rubber foam sealing strip material is solved by using expandable graphite, zinc borate, iron hydroxyoxide and cerium doped hydrotalcite and other materials. The problem of insufficient flame retardant performance and weak carbon layer strength achieve higher flame retardant and smoke suppression and sintering performance.
Patent Information
- Application Number
- CN202411244637.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The flame retardant performance of existing silicone rubber foam sealing strip materials is insufficient, and the carbon layer is weak after combustion, which cannot meet market demand.
By adding porcelain-assisted filler and porcelain-forming filler, the porcelain-assisted filler uses expandable graphite as the base material, with zinc borate intercalated, and iron hydroxyl oxides are grown on the surface, platinum particles and sulfhydryl groups are introduced to form a viscous liquid dehydrated at high temperature to fill the gaps , the hydroxy iron oxide in the ceramic filler forms a three-dimensional structure to improve adsorption capacity; the ceramic filler uses cerium-doped hydrotalcite as the substrate, and nanosilicon dioxide is grown in situ on the surface to form porous ceramics to improve refractory performance.
It significantly improves the flame retardant performance and fire resistance of foam sealing strip materials, improves the density of the carbon layer after combustion and the ability to absorb smoke, and enhances its flame retardant and smoke suppression effect and sintering performance.
Abstract
Description
Technical Field
[0001] The invention relates to the field of foaming sealing strip materials, and in particular to a foaming sealing strip material and a preparation method thereof. Background Art
[0002] Silicone rubber is a new type of polymer elastic material. The foam sealing strip made of silicone rubber is soft and elastic, has good high and low temperature resistance and electrical properties, and also has the advantages of light weight, weather resistance, small dielectric constant, good damping effect and thermal insulation performance. It is widely used in construction, chemical industry, electronics industry, transportation, aerospace and national defense.
[0003] However, due to the flammability of the molecular side chains in the foamed silicone rubber and the pore structure formed inside, a large amount of thick smoke will be generated in the event of a fire, posing a serious threat to the health and safety of personnel. It needs to be flame-retardant modified. Adding flame retardants is a common method to improve the flame retardant properties. However, due to the foaming structure of silicone rubber foam materials, the charcoal layer formed after combustion is extremely weak, and the flame retardant has limited improvement on its fire resistance, and cannot significantly improve the integrity and strength of the residual char after combustion, which cannot meet market demand. Summary of the invention
[0004] The purpose of the present invention is to provide a foam sealing strip material and a preparation method thereof, which solves the problem of insufficient flame retardancy of existing silicone rubber foam sealing strip materials and improves the problem of weak carbon layer strength and poor fire resistance of silicone rubber foam materials after combustion.
[0005] The object of the present invention can be achieved by the following technical scheme: Step S1: weigh the following raw materials in parts by weight: 80-100 parts of methyl vinyl silicone rubber, 15-20 parts of white carbon black, 20-30 parts of ceramic filler, 15-20 parts of ceramic filler, 6-8 parts of foaming agent and 1-2 parts of vulcanizing agent;
[0006] Step S2: Mixing methyl vinyl silicone rubber, white carbon black, ceramic filler, ceramic filler, foaming agent and vulcanizing agent, stirring at a stirring rate of 1000 rpm for 10 minutes, foaming at room temperature, and standing to obtain a foaming sealing strip material;
[0007] The ceramic-aiding filler is prepared by the following steps:
[0008] Step A1: expandable graphite, zinc borate and phosphoric acid solution are mixed, and potassium permanganate is added under stirring at a rate of 150-180 rpm and room temperature, and the reaction is carried out for 6-8 hours to obtain precursor I. Precursor I, ferric chloride hexahydrate and deionized water are mixed, and sodium sulfate is added under stirring at a rate of 120-150 rpm and a temperature of 120° C., and the reaction is carried out for 6-8 hours to obtain precursor II;
[0009] The mass fraction of phosphoric acid solution is 95%, the dosage ratio of expandable graphite, zinc borate, phosphoric acid solution and potassium permanganate is 18-21g: 0.8-1g: 100-110mL: 1.8-2g, and the dosage ratio of precursor I, ferric chloride hexahydrate, deionized water and sodium sulfate is 8-10g: 1.2-1.4g: 30-50mL: 0.4-0.5g;
[0010] During the reaction, potassium permanganate is used as an oxidant to destroy the van der Waals force between expandable graphite layers through chemical oxidation, so that the intercalation agents zinc borate and phosphoric acid are infiltrated into the expandable graphite layers to obtain precursor I. Since precursor I contains a large amount of hydroxyl groups, hexahydrated ferric chloride is used as an iron source through a hydrothermal method to generate rod-shaped hydroxyl iron oxide on the surface of precursor I to obtain precursor II.
[0011] Step A2: Cysteine, mono-6-O-(p-toluenesulfonyl)-β-cyclodextrin, deionized water and triethanolamine were mixed, and the mixture was reacted for 24 hours under nitrogen protection at a stirring rate of 120-150 rpm and a temperature of 85°C to obtain intermediate I. Intermediate I, potassium tetrachloroplatinate and deionized water were mixed, and the mixture was stirred for 24 hours at a stirring rate of 120-150 rpm and a temperature of 60°C, and then sodium borohydride solution was added, and the reaction was continued for 2-3 hours to obtain precursor III.
[0012] The amount ratio of cysteine, mono-6-O-(p-toluenesulfonyl)-β-cyclodextrin, deionized water and triethanolamine is 0.02-0.03 mol: 0.05-0.06 mol: 30-40 mL: 20-30 mL, the molar concentration of the sodium borohydride solution is 0.2 mol / L, and the amount ratio of intermediate I, potassium tetrachloroplatinate, deionized water and sodium borohydride solution is 0.02-0.03 mol: 0.008-0.01 mol: 50-60 mL: 3-4 mL;
[0013] During the reaction, the p-toluenesulfonyl group in mono-6-O-(p-toluenesulfonyl)-β-cyclodextrin is replaced by the amino group in cysteine to obtain an intermediate Ⅰ containing cysteine. Potassium tetrachloroplatinate is then used as a platinum source, and platinum ions form a complex with cysteine in the intermediate Ⅰ. The complex is then reduced with sodium borohydride to form platinum particles to obtain a precursor Ⅲ.
[0014] Step A3: Precursor II, precursor III, potassium carbonate and tetrahydrofuran are mixed, and stirred at a stirring rate of 80-100 rpm and a temperature of 85°C for 24 hours to obtain precursor IV. Precursor IV, terminal hydroxyl polymethylvinylsiloxane and tetrahydrofuran are mixed, and stirred at a stirring rate of 60-80 rpm and room temperature, and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is added, and then reacted under 365 nm ultraviolet light irradiation for 12 hours to obtain a ceramic filler;
[0015] The amount ratio of precursor II, precursor III, potassium carbonate and tetrahydrofuran is 0.1-0.12g: 0.2-0.3g: 0.15-0.18g: 50-60mL, and the amount ratio of precursor IV, terminal hydroxyl polymethylvinylsiloxane and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is 0.2-0.24g: 0.08-0.1g: 0.02g;
[0016] During the reaction, the precursor IV is prepared through the host-guest inclusion complex between the ferric hydroxide in the precursor II and the cyclodextrin in the precursor III, and then under the action of 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone and ultraviolet light, the thiol group in the precursor IV and the vinyl group in the terminal hydroxyl polymethylvinylsiloxane undergo addition reaction to prepare the ceramic filler;
[0017] The ceramic filler is prepared by the following steps:
[0018] Step B1: zinc nitrate hexahydrate, aluminum nitrate nonahydrate, cerium nitrate hexahydrate and deionized water are mixed, stirred at a stirring rate of 100-120 rpm at room temperature for 10-15 minutes, then sodium hydroxide and sodium carbonate are added, the temperature is raised to 65° C., stirring is continued for 12 hours, and drying is performed to obtain a precursor a;
[0019] The dosage ratio of zinc nitrate hexahydrate, aluminum nitrate nonahydrate, cerium nitrate hexahydrate, deionized water, sodium hydroxide and sodium carbonate is 65-68g: 25-26g: 18-20g: 200-220mL: 30-32g: 22-23g;
[0020] During the reaction, a precursor a containing a cerium-doped hydrotalcite structure was prepared by a hydrothermal method;
[0021] Step B2: Precursor a, sodium dodecylbenzene sulfonate and deionized water are mixed, stirred at a stirring rate of 100-120 rpm, at room temperature, and sodium silicate aqueous solution is added, stirred for 1 hour, and then ethanol and citric acid solution are added, and the temperature is raised to 80° C., reacted for 2-3 hours, and dried to obtain a porcelain filler;
[0022] The mass fraction of the sodium silicate aqueous solution is 25%, the molar concentration of the citric acid solution is 1 mol / L, and the amount ratio of the precursor a, sodium dodecylbenzene sulfonate, the sodium silicate aqueous solution and the citric acid solution is 60-65 g: 32-34 g: 300-320 mL: 90-100 mL;
[0023] During the reaction, sodium dodecylbenzene sulfonate is used as a surfactant to in-situ grow nano-silicon dioxide on the surface of precursor a to obtain a ceramic filler;
[0024] Beneficial effects of the invention: The invention discloses a foaming sealing strip material and a preparation method thereof. By adding a ceramic filler and a ceramic filler, the problem of insufficient flame retardancy of the existing silicone rubber foaming sealing strip material is solved, and at the same time, the problem of weak carbon layer strength and poor fire resistance of the silicone rubber foaming material after combustion is improved; the ceramic filler is based on expandable graphite, intercalated with zinc borate, and iron hydroxide grows on the surface, and then a precursor III containing platinum particles and thiol groups is introduced through the host-guest inclusion complex of iron hydroxide and cyclodextrin, and terminal hydroxyl polymethylvinylsiloxane is introduced through a click reaction between the thiol group and the double bond. During the combustion process of the foaming sealing strip material, under high temperature conditions, the zinc borate intercalated by the ceramic filler will be dehydrated to produce boric acid, which can further phase-transform into a molten viscous liquid at high temperature. This viscous liquid The invention can fill the gaps formed by the expansion of expandable graphite and the high-temperature carbonization of cyclodextrin, making the carbon layer denser. At the same time, the three-dimensional structure formed by the in-situ growth of ferric hydroxide can improve the adsorption capacity of the ceramic filler to smoke and improve its flame retardant and smoke suppression effect. When a fire occurs, since the ceramic filler contains platinum particles and terminal hydroxyl polymethylvinylsiloxane is introduced, which can react with the substrate methylvinyl silicone rubber during the room temperature foaming process, and the ceramic filler is based on cerium-doped hydrotalcite and has nano-silica grown in-situ on the surface, the combination of these two fillers forms a porous ceramic with supporting capacity, which greatly improves the fire resistance of the foamed sealing strip material. In addition, due to the high flame retardant properties of the ceramic filler's own substrate, the flame retardant ability of the foamed sealing strip material is also greatly improved. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1 Step S1: Weigh the following raw materials by weight: 80 parts of commercially available DY-V110-2 methyl vinyl silicone rubber, 15 parts of commercially available Sanjia white carbon black, 20 parts of ceramic fillers, 15 parts of ceramic fillers, 6 parts of commercially available KH0030 foaming agents and 1 part of commercially available TXC vulcanizing agent;
[0027] Step S2: Mixing methyl vinyl silicone rubber, white carbon black, ceramic filler, ceramic filler, foaming agent and vulcanizing agent, stirring at a stirring rate of 1000 rpm for 10 minutes, foaming at room temperature, and standing to obtain a foaming sealing strip material;
[0028] The ceramic-aiding filler is prepared by the following steps:
[0029] Step A1: Mix commercially available Marlin 200 mesh expandable graphite, zinc borate and phosphoric acid solution, stir at a stirring rate of 150 rpm, add potassium permanganate, and react for 6 hours to obtain precursor I; mix precursor I, ferric chloride hexahydrate and deionized water, stir at a stirring rate of 120 rpm, and add sodium sulfate at a temperature of 120° C., and react for 6 hours to obtain precursor II;
[0030] The mass fraction of phosphoric acid solution is 95%, the amount ratio of expandable graphite, zinc borate, phosphoric acid solution and potassium permanganate is 18g:0.8g:100mL:1.8g, and the amount ratio of precursor I, ferric chloride hexahydrate, deionized water and sodium sulfate is 8g:1.2g:30mL:0.4g;
[0031] Step A2: Cysteine, mono-6-O-(p-toluenesulfonyl)-β-cyclodextrin, deionized water and triethanolamine were mixed, and the mixture was reacted for 24 hours under nitrogen protection, at a stirring rate of 120 rpm and a temperature of 85°C to obtain intermediate I. Intermediate I, potassium tetrachloroplatinate and deionized water were mixed, and the mixture was stirred for 24 hours at a stirring rate of 120 rpm and a temperature of 60°C, and then sodium borohydride solution was added, and the reaction was continued for 2 hours to obtain precursor III.
[0032] The amount ratio of cysteine, mono-6-O-(p-toluenesulfonyl)-β-cyclodextrin, deionized water and triethanolamine is 0.02mol:0.05mol:30mL:20mL, the molar concentration of sodium borohydride solution is 0.2mol / L, and the amount ratio of intermediate I, potassium tetrachloroplatinate, deionized water and sodium borohydride solution is 0.02mol:0.008mol:50mL:3mL;
[0033] Step A3: Precursor II, precursor III, potassium carbonate and tetrahydrofuran are mixed, and stirred at a stirring rate of 80 rpm and a temperature of 85°C for 24 hours to obtain precursor IV. Precursor IV, commercially available 109-terminated hydroxyl polymethylvinylsiloxane and tetrahydrofuran are mixed, and stirred at a stirring rate of 60 rpm and room temperature, and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is added, and then reacted under 365 nm ultraviolet light irradiation for 12 hours to obtain a ceramic filler;
[0034] The amount ratio of precursor II, precursor III, potassium carbonate and tetrahydrofuran is 0.1g: 0.2-0.3g: 0.15g: 50mL, and the amount ratio of precursor IV, terminal hydroxyl polymethylvinylsiloxane and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is 0.2g: 0.08g: 0.02g;
[0035] The ceramic filler is prepared by the following steps:
[0036] Step B1: zinc nitrate hexahydrate, aluminum nitrate nonahydrate, cerium nitrate hexahydrate and deionized water are mixed, stirred at a stirring rate of 100 rpm at room temperature for 10 minutes, then sodium hydroxide and sodium carbonate are added, the temperature is raised to 65° C., stirring is continued for 12 hours, and drying is performed to obtain a precursor a;
[0037] The dosage ratio of zinc nitrate hexahydrate, aluminum nitrate nonahydrate, cerium nitrate hexahydrate, deionized water, sodium hydroxide and sodium carbonate is 65g:25g:18g:200mL:30g:22g;
[0038] Step B2: Precursor a, sodium dodecylbenzene sulfonate and deionized water were mixed, stirred at a stirring rate of 100 rpm, and sodium silicate aqueous solution was added at room temperature, stirred for 1 hour, and then ethanol and citric acid solution were added, and the temperature was raised to 80° C., reacted for 2 hours, and dried to obtain a porcelain filler;
[0039] The mass fraction of the sodium silicate aqueous solution is 25%, the molar concentration of the citric acid solution is 1 mol / L, and the amount ratio of precursor a, sodium dodecylbenzene sulfonate, sodium silicate aqueous solution and citric acid solution is 60g:32g:300mL:90mL.
[0040] Example 2 Step S1: Weigh the following raw materials in parts by weight: 80 parts of commercially available DY-V110-2 methyl vinyl silicone rubber, 20 parts of commercially available Sanjia white carbon black, 20 parts of ceramic filler, 15 parts of ceramic filler, 8 parts of commercially available KH0030 foaming agent and 2 parts of commercially available TXC vulcanizing agent;
[0041] Step S2: Mixing methyl vinyl silicone rubber, white carbon black, ceramic filler, ceramic filler, foaming agent and vulcanizing agent, stirring at a stirring rate of 1000 rpm for 10 minutes, foaming at room temperature, and standing to obtain a foaming sealing strip material;
[0042] The ceramic-aiding filler is prepared by the following steps:
[0043] Step A1: Mix commercially available Marlin 200 mesh expandable graphite, zinc borate and phosphoric acid solution, stir at a stirring rate of 180 rpm, add potassium permanganate, and react for 8 hours to obtain precursor I. Mix precursor I, ferric chloride hexahydrate and deionized water, stir at a stirring rate of 120 rpm, and add sodium sulfate at a temperature of 120° C., and react for 6 hours to obtain precursor II;
[0044] The mass fraction of phosphoric acid solution is 95%, the amount ratio of expandable graphite, zinc borate, phosphoric acid solution and potassium permanganate is 21g:0.8g:110mL:1.8g, and the amount ratio of precursor I, ferric chloride hexahydrate, deionized water and sodium sulfate is 8g:1.4g:30mL:0.5g;
[0045] Step A2: Cysteine, mono-6-O-(p-toluenesulfonyl)-β-cyclodextrin, deionized water and triethanolamine were mixed, and the mixture was reacted for 24 hours under nitrogen protection, at a stirring rate of 120-150 rpm and a temperature of 85°C to obtain intermediate I. Intermediate I, potassium tetrachloroplatinate and deionized water were mixed, and the mixture was stirred for 24 hours at a stirring rate of 150 rpm and a temperature of 60°C, and then sodium borohydride solution was added, and the reaction was continued for 2 hours to obtain precursor III.
[0046] The amount ratio of cysteine, mono-6-O-(p-toluenesulfonyl)-β-cyclodextrin, deionized water and triethanolamine is 0.03 mol: 0.05 mol: 40 mL: 20 mL, the molar concentration of sodium borohydride solution is 0.2 mol / L, and the amount ratio of intermediate I, potassium tetrachloroplatinate, deionized water and sodium borohydride solution is 0.02 mol: 0.01 mol: 50 mL: 4 mL;
[0047] Step A3: Precursor II, precursor III, potassium carbonate and tetrahydrofuran are mixed, and stirred at a stirring rate of 100 rpm and a temperature of 85°C for 24 hours to obtain precursor IV. Precursor IV, commercially available 109-terminated hydroxyl polymethylvinylsiloxane and tetrahydrofuran are mixed, and stirred at a stirring rate of 60 rpm and room temperature, and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is added, and then reacted under 365 nm ultraviolet light irradiation for 12 hours to obtain a ceramic filler;
[0048] The amount ratio of precursor II, precursor III, potassium carbonate and tetrahydrofuran is 0.1g:0.3g:0.18g:50mL, the amount ratio of precursor IV, terminal hydroxyl polymethylvinylsiloxane and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is 0.2g:0.1g:0.02g;
[0049] The ceramic filler is prepared by the following steps:
[0050] Step B1: zinc nitrate hexahydrate, aluminum nitrate nonahydrate, cerium nitrate hexahydrate and deionized water are mixed, stirred at a stirring rate of 120 rpm at room temperature for 10 min, then sodium hydroxide and sodium carbonate are added, the temperature is raised to 65° C., stirring is continued for 12 h, and drying is performed to obtain a precursor a;
[0051] The usage ratio of zinc nitrate hexahydrate, aluminum nitrate nonahydrate, cerium nitrate hexahydrate, deionized water, sodium hydroxide and sodium carbonate is 65g:26g:18g:220mL:32g:22g;
[0052] Step B2: Precursor a, sodium dodecylbenzene sulfonate and deionized water were mixed, stirred at a stirring rate of 100 rpm, and sodium silicate aqueous solution was added at room temperature, stirred for 1 hour, and then ethanol and citric acid solution were added, and the temperature was raised to 80° C., reacted for 3 hours, and dried to obtain a porcelain filler;
[0053] The mass fraction of the sodium silicate aqueous solution is 25%, the molar concentration of the citric acid solution is 1 mol / L, and the amount ratio of precursor a, sodium dodecylbenzene sulfonate, sodium silicate aqueous solution and citric acid solution is 65g:34g:300mL:100mL.
[0054] Example 3 Step S1: Weigh the following raw materials in parts by weight: 100 parts of commercially available DY-V110-2 methyl vinyl silicone rubber, 20 parts of commercially available Sanjia white carbon black, 30 parts of ceramic fillers, 20 parts of ceramic fillers, 8 parts of commercially available KH0030 foaming agent and 2 parts of commercially available TXC vulcanizing agent;
[0055] Step S2: Mixing methyl vinyl silicone rubber, white carbon black, ceramic filler, ceramic filler, foaming agent and vulcanizing agent, stirring at a stirring rate of 1000 rpm for 10 minutes, foaming at room temperature, and standing to obtain a foaming sealing strip material;
[0056] The ceramic-aiding filler is prepared by the following steps:
[0057] Step A1: Mix commercially available Marlin 200 mesh expandable graphite, zinc borate and phosphoric acid solution, stir at a stirring rate of 180 rpm, add potassium permanganate, and react for 8 hours to obtain precursor I; mix precursor I, ferric chloride hexahydrate and deionized water, stir at a stirring rate of 150 rpm, and add sodium sulfate at a temperature of 120° C., and react for 8 hours to obtain precursor II;
[0058] The mass fraction of phosphoric acid solution is 95%, the amount ratio of expandable graphite, zinc borate, phosphoric acid solution and potassium permanganate is 21g:1g:110mL:2g, and the amount ratio of precursor I, ferric chloride hexahydrate, deionized water and sodium sulfate is 10g:1.4g:50mL:0.5g;
[0059] Step A2: Cysteine, mono-6-O-(p-toluenesulfonyl)-β-cyclodextrin, deionized water and triethanolamine were mixed, and the mixture was reacted for 24 hours under nitrogen protection, at a stirring rate of 150 rpm and a temperature of 85°C to obtain intermediate I. Intermediate I, potassium tetrachloroplatinate and deionized water were mixed, and the mixture was stirred for 24 hours at a stirring rate of 150 rpm and a temperature of 60°C, and then sodium borohydride solution was added, and the reaction was continued for 3 hours to obtain precursor III.
[0060] The amount ratio of cysteine, mono-6-O-(p-toluenesulfonyl)-β-cyclodextrin, deionized water and triethanolamine is 0.03 mol: 0.06 mol: 40 mL: 30 mL, the molar concentration of sodium borohydride solution is 0.2 mol / L, and the amount ratio of intermediate I, potassium tetrachloroplatinate, deionized water and sodium borohydride solution is 0.03 mol: 0.01 mol: 60 mL: 4 mL;
[0061] Step A3: Precursor II, precursor III, potassium carbonate and tetrahydrofuran are mixed, and stirred at a stirring rate of 100 rpm and a temperature of 85°C for 24 hours to obtain precursor IV. Precursor IV, commercially available 109-terminated hydroxyl polymethylvinylsiloxane and tetrahydrofuran are mixed, and stirred at a stirring rate of 80 rpm and room temperature, and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is added, and then reacted under 365 nm ultraviolet light irradiation for 12 hours to obtain a ceramic filler;
[0062] The amount ratio of precursor II, precursor III, potassium carbonate and tetrahydrofuran is 0.12g:0.3g:0.18g:60mL, the amount ratio of precursor IV, terminal hydroxyl polymethylvinylsiloxane and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is 0.24g:0.1g:0.02g;
[0063] The ceramic filler is prepared by the following steps:
[0064] Step B1: zinc nitrate hexahydrate, aluminum nitrate nonahydrate, cerium nitrate hexahydrate and deionized water are mixed, stirred at a stirring rate of 120 rpm at room temperature for 15 minutes, then sodium hydroxide and sodium carbonate are added, the temperature is raised to 65° C., stirring is continued for 12 hours, and drying is performed to obtain a precursor a;
[0065] The usage ratio of zinc nitrate hexahydrate, aluminum nitrate nonahydrate, cerium nitrate hexahydrate, deionized water, sodium hydroxide and sodium carbonate is 68g:26g:20g:220mL:32g:23g;
[0066] Step B2: Precursor a, sodium dodecylbenzene sulfonate and deionized water were mixed, stirred at a stirring rate of 120 rpm, and sodium silicate aqueous solution was added at room temperature, stirred for 1 hour, and then ethanol and citric acid solution were added, and the temperature was raised to 80° C., reacted for 3 hours, and dried to obtain a porcelain filler;
[0067] The mass fraction of the sodium silicate aqueous solution is 25%, the molar concentration of the citric acid solution is 1 mol / L, and the amount ratio of precursor a, sodium dodecylbenzene sulfonate, sodium silicate aqueous solution and citric acid solution is 65g:34g:320mL:100mL.
[0068] Comparative Example 1 Compared with Example 3, this comparative example is different in that the precursor III in the preparation process of the ceramic-aiding filler in Example 3 is replaced by the intermediate I in Example 3, and the other steps are the same.
[0069] Comparative Example 2 Compared with Example 3, this comparative example is characterized in that the precursor II in the preparation process of the ceramic-aiding filler in Example 3 is replaced by the precursor I in Example 3, and the other steps are the same.
[0070] Comparative Example 3 Compared with Example 3, this comparative example is to remove the terminal hydroxyl polymethylvinylsiloxane in the preparation process of the ceramic-aiding filler in Example 3, and the other steps are the same.
[0071] Comparative Example 4 Compared with Example 3, this comparative example is different in that the ceramic filler in the preparation process of the foamed sealing strip material in Example 3 is replaced with commercially available D200 magnesium aluminum hydrotalcite, and the other steps are the same.
[0072] Take the foam sealing strip materials prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, and make the foam sealing strip materials into 100mm×10mm×3mm samples. Refer to GB / T 10707-2008 to test the limiting oxygen index and vertical combustion grade thereof. Refer to ISO 5660-1 and use a cone calorimeter at an irradiation intensity of 35kW / m 2Under the conditions, its combustion behavior was recorded and tested. The foam sealing strip material was made into a 50mm×10mm×6mm sample, sintered at 600℃ in a muffle furnace for 2h, and the compression strength of the ablated product when it was destroyed was measured by a universal testing machine. The maximum force required to destroy the sample was used to characterize its sintering performance. The test results are shown in the following table:
[0073] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Limiting oxygen index (%) 32.9 33.2 33.6 33.5 28.9 30.9 31.2 Vertical burning level V-0 V-0 V-0 V-0 V-2 V-1 V-0 <![CDATA[Total smoke release amount (m 2 ·m -2 )]]> 1.31 1.28 1.26 1.28 9.18 3.65 4.30 Sintering strength (N) 785.6 788.9 789.2 721.6 601.7 668.4 631.5
[0074] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, Comparative Example 1 replaces the precursor III in the preparation process of the ceramic filler in Example 3 with the intermediate I in Example 3. Due to the lack of platinum doping, its ceramicization performance is reduced, thereby affecting its sintering strength. Comparative Example 2 replaces the precursor II in the preparation process of the ceramic filler in Example 3 with the precursor I in Example 3. Due to the lack of ferric hydroxide, it cannot undergo host-guest inclusion complexation with cyclodextrin, thereby affecting its flame retardant and smoke suppression properties and sintering strength. Comparative Example 3 removes the terminal hydroxyl polymethylvinylsiloxane in the preparation process of the ceramic filler in Example 3. Due to the lack of terminal hydroxyl polymethylvinylsiloxane, it lacks chemical bonds with the matrix, thereby affecting its various properties. Comparative Example 4 replaces the ceramic filler in the preparation process of the foaming sealing strip material in Example 3 with commercially available magnesium aluminum hydrotalcite. Due to the lack of cerium doping and nano-silica, its sintering strength is greatly reduced.
[0075] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0076] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a foam sealing strip material, characterized in that: The method comprises the following steps: Step S1: weighing the following raw materials in parts by weight: 80-100 parts of methyl vinyl silicone rubber, 15-20 parts of white carbon black, 20-30 parts of ceramic-assisting filler, 15-20 parts of ceramic-forming filler, 6-8 parts of foaming agent and 1-2 parts of vulcanizing agent; Step S2: Mixing methyl vinyl silicone rubber, white carbon black, ceramic filler, ceramic filler, foaming agent and vulcanizing agent, stirring at a stirring rate of 1000 rpm for 10 minutes, foaming at room temperature, and standing to obtain a foaming sealing strip material; The ceramic-aiding filler is prepared by the following steps: Step A1: expandable graphite, zinc borate and phosphoric acid solution are mixed, and potassium permanganate is added under stirring at a rate of 150-180 rpm and room temperature, and the mixture is reacted for 6-8 hours to obtain precursor 1; precursor 1, ferric chloride hexahydrate and deionized water are mixed, and sodium sulfate is added under stirring at a rate of 120-150 rpm and a temperature of 120° C., and the mixture is reacted for 6-8 hours to obtain precursor 2; Step A2: Cysteine, mono-6-O-(p-toluenesulfonyl)-β-cyclodextrin, deionized water and triethanolamine were mixed, and the mixture was reacted for 24 hours at a stirring rate of 120-150 rpm and a temperature of 85°C under nitrogen protection to obtain intermediate 1. Intermediate 1, potassium tetrachloroplatinate and deionized water were mixed, and the mixture was stirred for 24 hours at a stirring rate of 120-150 rpm and a temperature of 60°C. Then, sodium borohydride solution was added and the reaction was continued for 2-3 hours to obtain precursor 3. Step A3: Precursor 2, precursor 3, potassium carbonate and tetrahydrofuran are mixed, and stirred at a stirring rate of 80-100 rpm and a temperature of 85°C for 24 hours to obtain precursor 4; Precursor 4, terminal hydroxyl polymethylvinylsiloxane and tetrahydrofuran are mixed, and stirred at a stirring rate of 60-80 rpm and room temperature, and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is added, and then reacted under 365 nm ultraviolet light irradiation for 12 hours to obtain a ceramic filler; The ceramic filler is prepared by the following steps: Step B1: zinc nitrate hexahydrate, aluminum nitrate nonahydrate, cerium nitrate hexahydrate and deionized water are mixed, stirred at a stirring rate of 100-120 rpm at room temperature for 10-15 minutes, then sodium hydroxide and sodium carbonate are added, the temperature is raised to 65° C., stirring is continued for 12 hours, and drying is performed to obtain a precursor a; Step B2: Mix precursor a, sodium dodecylbenzene sulfonate and deionized water, stir at a stirring rate of 100-120 rpm, add sodium silicate aqueous solution at room temperature, stir for 1 hour, then add ethanol and citric acid solution, heat to 80°C, react for 2-3 hours, and dry to obtain a porcelain filler.
2. The method for preparing a foam sealing strip material according to claim 1, characterized in that: In step A1: the mass fraction of the phosphoric acid solution is 95%, the amount ratio of expandable graphite, zinc borate, phosphoric acid solution and potassium permanganate is 18-21g: 0.8-1g: 100-110mL: 1.8-2g, and the amount ratio of precursor 1, ferric chloride hexahydrate, deionized water and sodium sulfate is 8-10g: 1.2-1.4g: 30-50mL: 0.4-0.5g.
3. The method for preparing a foam sealing strip material according to claim 1, characterized in that: In step A2, the amount ratio of cysteine, mono-6-O-(p-toluenesulfonyl)-β-cyclodextrin, deionized water and triethanolamine is 0.02-0.03 mol: 0.05-0.06 mol: 30-40 mL: 20-30 mL, the molar concentration of the sodium borohydride solution is 0.2 mol / L, and the amount ratio of the intermediate 1, potassium tetrachloroplatinate, deionized water and sodium borohydride solution is 0.02-0.03 mol: 0.008-0.01 mol: 50-60 mL: 3-4 mL.
4. The method for preparing a foam sealing strip material according to claim 1, characterized in that: In step A3: the amount ratio of precursor 2, precursor 3, potassium carbonate and tetrahydrofuran is 0.1-0.12g: 0.2-0.3g: 0.15-0.18g: 50-60mL, and the amount ratio of precursor 4, terminal hydroxyl polymethylvinylsiloxane and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is 0.2-0.24g: 0.08-0.1g: 0.02g.
5. The method for preparing a foam sealing strip material according to claim 1, characterized in that: In step B1, the usage ratio of zinc nitrate hexahydrate, aluminum nitrate nonahydrate, cerium nitrate hexahydrate, deionized water, sodium hydroxide and sodium carbonate is 65-68 g: 25-26 g: 18-20 g: 200-220 mL: 30-32 g: 22-23 g.
6. The method for preparing a foam sealing strip material according to claim 1, characterized in that: In step B2: the mass fraction of the sodium silicate aqueous solution is 25%, the molar concentration of the citric acid solution is 1 mol / L, and the amount ratio of precursor a, sodium dodecylbenzene sulfonate, sodium silicate aqueous solution and citric acid solution is 60-65g:32-34g:300-320mL:90-100mL.
7. A foam sealing strip material, characterized in that: Prepared according to any one of claims 1 to 6.
Citation Information
Patent Citations
Porcelainized fireproof and heat insulation foamed silicone rubber and preparation method thereof
CN109467936A